LEFT VENTRICULAR HYPERTROPHY: DIAGNOSIS IN 40-60-YEAR-OLD WOMEN WITH HYPERTENSION - Naimov D.K (Journal Park Publishing, 2022)
This article describes a clinical study conducted among patients on an outpatient basis on the basis of the "Bukhara Regional Cardiology Dispensary". The features of hypertrophy of the left ventricle of the heart by concentric, eccentric types were revealed.
Keywords: 40-60 years old; left ventricular hypertrophy; echocardiography